Cerebral oximetry monitoring by means of INVOS-4100 as a predictor of ischemic events during carotid endarterectomy - Russo, Maria Francesca; Gentile, Patrizia; Fenga, Marco; Izzo, Silvia; Denaro, Flavia; Luka, Klaudia; Frattaroli, Flaminia; Costanzo, Alessandro; Castagneto-Gissey, Lidia; Salvati, Bruno (Frontiers in Surgery, 2023)
Background: Several methods have been proposed to monitor cerebral perfusion during carotid endarterectomy (CEA), with the purpose of minimizing the risk of perioperative stroke. The INVOS-4100 is able to detect cerebral oxygen saturation providing an intraoperative real-time monitoring system of cerebral oximetry. The aim of this study was to evaluate the performance of the INVOS-4100 in predicting cerebral ischemia during CEA. Methods: Between January 2020 and May 2022, 68 consecutive patients were scheduled for CEA either under general anesthesia or regional anesthesia with deep and superficial cervical block. Vascular oxygen saturation was recorded continually through INVOS before and during clamping of the ICA. Awake testing was performed in the group of patients undergoing CEA under regional anesthesia. Results: Sixty-eight patients were included; 43 were males (63.2%). Severe stenosis of the artery was present in 92%. Forty-one (60.3%) patients were monitored by INVOS, while 22 (39.7%) underwent awake testing. Mean clamping time was 20±6.6min. Patients undergoing awake testing had a lower hospital stay and ICU stay during admission (p=0.011 and p=0.007 respectively). Comorbidities correlated with a higher ICU stay (p<0.05). The INVOS monitoring was able to predict ischemic events with a sensitivity of 98% (AUC = 0.976). Conclusions: The present study demonstrates that cerebral oximetry monitoring was a strong predictor of cerebral ischemia, although it was not possible to determine the non-inferiority of cerebral oximetry compared to awake testing. Nonetheless, the use of cerebral oximetry evaluates only perfusion in the superficial brain tissue and an absolute rSO2 value corresponding to significant cerebral ischemia has not been established. Therefore, larger prospective studies that correlate cerebral oximetry with neurologic outcomes are needed.